The double-lined spectroscopic binary orbit of the massive supergiant HD 152147: A new target for interferometry. Issue 2 (21st October 2022) - Putkuri, C; Gamen, R; Benvenuto, O G; Morrell, N I; Barbá, R H; Higa, R; Arias, J I
ABSTRACT: We present a new spectroscopic orbit of the O-type binary system HD 152147. We identify absorption lines in both components and use their radial velocities to determine the orbit, which results in a period of P = 50.2199 ± 0.0007 d, an eccentricity e = 0.738 ± 0.007, and a mean separation between the components of a sin i = 151 ± 1 R⊙ . Considering that the distance to the system is 1600 pc, this implies an angular separation of ∼0.44 mas, making it suitable for modern interferometric observations. In addition, we determine the fundamental stellar parameters of each component by means of a quantitative spectral analysis. We obtain M a = 31.9−34.6 M⊙ and R a = 17−24 R⊙ for the primary, and M b = 14−15 M⊙ and R b = 5−10 R⊙ for the secondary. We apply models with rotation to try to characterize the evolutionary status of the HD 152147 system. We find that the two components are compatible with a common age of 4.5 Myr. We also detect variations in the profile of Hα that are not modulated by the orbital cycle. Moreover, TESS photometry also presents intrinsic variability and was analysed for periodicities. We find a most relevant frequency of 20 times the orbital one, in a TESS data set that includes the periastron passage, and we interpret it as a tidally induced pulsation that seems to dissipate on a time-scale shorter than the orbital cycle because it is not present in another TESS data set that nearly covers the apoastron.